KOMISARIS INDEPENDEN, KOMITE AUDIT, INTERNAL AUDIT DAN RISK MANAGEMENT COMMITTEE TERHADAP MANAJEMEN LABA - Nurika Restuningdiah (University of Merdeka Malang, 2011)
The purpose of this research was to examine the impact of independency of board commisioner, audit committee,internal audit and risk management comittee to earning management. Regression Analysis of 35 publiccompanies listing in Indonesia Stock Exchange on year 2009 through a random sampling technique indicatedthat there was no significant impact of independency of board commisioner, audit committee, internal auditand risk management comittee to earning management. The implication of this study was relevant to thedecision maker of public companies to consider the skill and expertise of board commisioner, audit committe,internal audit and risk management comittee to support the internal corporate governance mechanism.